1996
DOI: 10.1007/bf01986275
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen losses and fertilizer N use efficiency in irrigated porous soils

Abstract: Porous soils are characterized by high infiltration, low moisture retention and poor fertility due to limitation of organic matter and nitrogen (N). However, wherever irrigated and properly managed, these are among the most productive soils in the world. For sustained productivity and prevention of N related pollution problems, fertilizer N management in porous soils needs to be improved by reducing losses of N via different mechanisms. Losses of N through ammonia volatilization are not favoured in porous soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(58 citation statements)
references
References 52 publications
2
56
0
Order By: Relevance
“…These may include increased plant stress resulting in low nitrate uptake and low crop yields (Groves and Bailey, 1997), decreased microbial processes resulting in more limited denitrification (Ashby et al, 1998;de Klein and van Logtestijn, 1996) and decreased runoff and leaching (Emmerich and Heitschmidt, 2002;Stites and Kraft, 2001). The timing of fertilizer application before or after a rainfall or irrigation event also influences the amount of available nitrate in the soil (Aulakh and Bijay-Singh, 1997). Additionally, droughts and periods of low flow typically coincide with lowered water tables, decreased hydrologic storage, and decreased hydrologic connectivity, all of which inhibit nitrate transport to streams (Bernal and Sabater, 2012;Detty and McGuire, 2010;Macrae et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These may include increased plant stress resulting in low nitrate uptake and low crop yields (Groves and Bailey, 1997), decreased microbial processes resulting in more limited denitrification (Ashby et al, 1998;de Klein and van Logtestijn, 1996) and decreased runoff and leaching (Emmerich and Heitschmidt, 2002;Stites and Kraft, 2001). The timing of fertilizer application before or after a rainfall or irrigation event also influences the amount of available nitrate in the soil (Aulakh and Bijay-Singh, 1997). Additionally, droughts and periods of low flow typically coincide with lowered water tables, decreased hydrologic storage, and decreased hydrologic connectivity, all of which inhibit nitrate transport to streams (Bernal and Sabater, 2012;Detty and McGuire, 2010;Macrae et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 25 percent of cropland in the Missouri River basin is irrigated, making it the most irrigated basin in this study (Table 1). During droughts, irrigation may remove nitrate from the soil horizon by leaching, denitrification, or uptake by crops (Aulakh and Bijay-Singh, 1997;Dinnes et al, 2002). Leached nitrate typically moves downward below the active root zone, leading to elevated nitrate concentrations in groundwater (Burkart and Stoner, 2008;Stites and Kraft, 2001).…”
Section: Relationships At Mid-high and High Contemporaneous Flowsmentioning
confidence: 99%
“…One such example is northwestern India where relatively high solar radiation, together with irrigation and nutrient inputs, enables the porous soils to be very productive (Aulakh and Bij ay-Singh, 1997). Irrigation and rain can transport urea N and ammoniacal N following fertilization into soil where it is more prone to nitrifi cation-denitrifi cation than NH 3 volatilization.…”
Section: Leachingmentioning
confidence: 99%
“…Indeed, experiments with partial NH 4 + and NO 3 − supply and model calculations revealed that NO 3 − absorption and assimilation by wetland plants like rice is particularly efficient (Kronzucker et al 1999;Kronzucker et al 2000;Kirk and Kronzucker 2005;Duan et al 2007). Nevertheless, the agronomic practice of alternating flooding and draining of paddy rice fields may cause loss of up to 50% of applied N via nitrification-denitrification processes (Aulakh and BijaySingh 1997). Most land plant species (70 to 90%), including wetland and semi-aquatic plants, gain access to limited mineral nutrient resources when forming symbiotic associations with arbuscular mycorrhizal fungi (AMF) (Smith and Read 2008).…”
Section: Introductionmentioning
confidence: 99%